Early detection of first degree relatives to type-II diabetes mellitus - shanon, Abdul-Kareem; Jaddou, Betool (Iraqi National Journal of Nursing Specialties, 2011)
Objective(s): The study aims to assess the early detection of early detection of first degree relatives to type-IIdiabetes mellitus throughout the diagnostic tests of Glycated Hemoglobin A1C. (HgbA1C), Oral Glucose ToleranceTest (OGTT) and to find out the relationship between demographic data and early detection of first degreerelatives to type-II diabetes mellitus.Methodology: A purposive "non-probability" sample of (200) subjects first degree relatives to type-II diabetesmellitus was selected from National Center for Diabetes Mellitus/Al-Mustansria University and Specialist Centerfor Diabetes Mellitus and Endocrine Diseases/Al-kindy. These related persons have presented the age of (40-70)years old. A questionnaire was constructed for the purpose of the study, it is composed of (3) major parts, andoverall items, which are included in the questionnaire are (76) items. Reliability and validity of the questionnairewere determined through a pilot study which is carried out during the period of August, 1st, 2008 to February, 30th2009. The study instrument and structured interview technique were used as means of data collection. The datawere analyzed through the application of the descriptive statistical data analysis approach (Frequency andPercentage) and the inferential statistical data analysis approach Chi-square, Pearson correlation coefficient.Results: The results of the study confirmed that the mean of age is (55.7) year, and the majority of the sample aremale, first degree relatives with diabetes mellitus type-II are within positive bio-social aspect and laboratoryscreening had an effect on the incidence of diabetes mellitus type-II for first degree relatives to type-II diabetesmellitus.Recommendations: The study recommends that the number of diabetes centers should be increased in Baghdadand Governorates, promote of HbA1c test from general hospitals laboratories, guide notebook about thepredisposing factors of diabetes mellitus in his family, periodic screening for pre-diabetes and diabetes in high risk,asymptomatic, undiagnosed adults within the health care setting, prevention program to prevent and control onthe predisposing risk factors for nondependent diabetes mellitus type-II and complication